MANAJEMEN PENYELENGGARAAN PENGELOLAAN OBYEK WISATA AIR TERJUN RESUN DI KABUPATEN LINGGA - Abdul Hadi Baasit; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The background in this research is that the management of Resun waterfall tourism is still lack of organized arrangement and restoration of the area Resun waterfall. It looks unavailability of direct transportation to the area attractions, facilities such as shops souvenirs, lodging, tour guides are not available as an addition to the attractiveness of a tourist attraction. so that situation can affect attitudes, opportunities and interests of the visitors to come and enjoy the object and the existing facilities at Resun waterfall tourism.The purpose of this research is to determine the Object Management of Resun waterfall in Lingga District, and to determine the factors that influence the Object Management of Resun waterfall in Lingga District. The indicators used in this research is the application of Fayol hendry opinion in hasibuan that management can be measured by the following indicators: planning, organizing, actuating, controlling, including indicators to determine the factors that influence the management of tourism management.Type of method used in this research is descriptive qualitative. In determining the informant subsequently determined by purposive sampling technique, which the determination is based on the consideration that the informants were selected are people who know and involved in the management of Resun waterfall in Lingga District. To collect data, this reserach using interviews, observation, and documentation.Based on the result revealed that the management of Resun waterfall tourism in the Lingga District is "not maximized", whereas the factors that influence the management of Resun waterfall tourism in Lingga regency is human resources, infrastructure, and funding.Keywords: Organization, Management